Northwest Africa 8418: The first CV4 chondrite. (16th January 2023) - MacPherson, G. J.; Nagashima, K.; Krot, A. N.; Kuehner, S. M.; Irving, A. J.; Ziegler, K.; Mallozzi, L.; Corrigan, C.; Pitt, D.
Abstract: Northwest Africa (NWA) 8418 is an unusual chondrite whose properties do not exactly match those of any other known chondrite. It has similarities to the CV (Vigarano group), CK (Karoonda group), and CL (Loongana group) chondrites, but its abundance of large calcium‐aluminum‐rich inclusions (CAIs) and the low NiO content (<0.2 wt%) of its matrix olivine ally it most closely with the CV group. The absence of grossular, monticellite, wollastonite, and sodalite from the alteration products of the CAIs; the magnesium‐rich nature of the matrix olivines (Fa38 ) relative to that of the CV3 chondrites ( Fa50 ); and the presence of secondary Na‐bearing plagioclase and chlorapatite indicate a metamorphic temperature >600 °C. NWA 8418 contains kamacite, taenite, and troilite, and lacks magnetite and pentlandite. We propose that NWA 8418 be reclassified as a reduced CV4 chondrite, which makes it the first CV chondrite of petrologic type 4.